Tantangan dan Peluang Menuju Ekonomi Inklusif dalam Upaya Menjangkau Generasi Milenial - Meyla Nur Vita Sari (Program Studi Ekonomi Syariah Institut Agama Islam Sunan Kalijogo Malang, 2025)
Sharia economics in Indonesia holds significant potential to drive inclusive national economic growth, especially considering that approximately 87% of the population is Muslim. However, the development of this sector still faces fundamental challenges, such as low levels of Islamic financial literacy, limited access to Sharia-based financing for MSMEs, and suboptimal digital integration between the financial and real sectors. This study reveals that although millennials exhibit a high level of digital technology adoption and show interest in ethical, riba-free financial principles, there remains a significant information gap. The lack of understanding of Islamic economic principles prevents this productive age group from fully utilizing the potential of the Sharia economy. Millennials tend to be interested in Sharia financial products if those products offer ease of use, convenience, and competitive digital features. Moreover, social values such as justice, sustainability, and community concern also serve as strong motivators in their choice of Sharia-compliant services. Nevertheless, concerns over data security, the lack of clarity in legal and fatwa rulings on digital products, and the perception of limited innovation in Sharia products remain serious obstacles. Therefore, synergy between the government, Sharia financial institutions, and digital industry players is crucial to enhance education, strengthen regulations, and develop Sharia products that are adaptive and relevant to younger generations in the effort to achieve an inclusive economy.